Students' perceptions toward online learning in EFL Speaking - Tusino Tusino (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2022)
Although there have been numerous studies on online learning in language classes, fewer studies focus on EFL speaking. This qualitative case study aimed at describing students’ perceptions toward the implementation of online learning in speaking classes. The participants were EFL students taking a speaking course in an Indonesian university. Open-response questionnaires and semi-structured interviews were employed. The results showed that students had positive attitudes toward online learning through a Zoom application. It was also found that some challenges arose toward the implementation of online learning. It is suggested that the lecturers should emphasize more on collaborative and blended learning in teaching EFL speaking.